2013
DOI: 10.1159/000343449
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Recording and Evaluation of Pharmaco-Sleep Studies in Man: The International Pharmaco-EEG Society (IPEG)

Abstract: The International Pharmaco-EEG Society (IPEG) presents guidelines summarising the requirements for the recording and computerised evaluation of pharmaco-sleep data in man. Over the past years, technical and data-processing methods have advanced steadily, thus enhancing data quality and expanding the palette of sleep assessment tools that can be used to investigate the activity of drugs on the central nervous system (CNS), determine the time course of effects and pharmacodynamic properties of novel therapeutics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 528 publications
(301 reference statements)
0
28
0
Order By: Relevance
“…Specific recommendations for pharmaco-PSG studies can be found in the ‘Guidelines for the recording and evaluation of pharmaco-sleep studies in man: the International Pharmaco-EEG Society' [24]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific recommendations for pharmaco-PSG studies can be found in the ‘Guidelines for the recording and evaluation of pharmaco-sleep studies in man: the International Pharmaco-EEG Society' [24]. …”
Section: Resultsmentioning
confidence: 99%
“…Recommendations, specifically intended for pharmaco-sleep studies in man, for subject selection, environmental conditions and recording settings including adaptation nights as well as for digital recordings, calibration and biosignals, can be found in the ‘Guidelines for the recording and evaluation of pharmaco-sleep studies in man' recently published by the International Pharmaco-EEG Society [24]. …”
Section: Recordingmentioning
confidence: 99%
“…Secondly, it is essential to have an appropriate database at one's disposal to compare how variable the effects of a specific drug are within a drug class as well as over drug classes. To date, in contrast to clinical p-(sleep) EEG [98,99], there are no general recording or analysis principles in animal p-EEG and p-sleep EEG, which makes it difficult to compare drug effects between laboratories. Since most labs have already build up a consistent, homogeneous database of p-EEG effects it is a real challenge to define such principles, as most labs want to stick to their own standards.…”
Section: Methodological Standardisationmentioning
confidence: 99%
“… 1 Such guidelines are presently being prepared de novo as a follow-up to the IPEG human guidelines which have already appeared [98,99]: with this paper the IPEG would also like to invite people who think they can further contribute to the formulation of such guidelines to contact the first author. …”
mentioning
confidence: 99%
“…Guidelines for the recording and evaluation of pharmaco-EEG studies and of pharmaco-sleep studies have been published in this journal in 2012 and 2013, respectively [14,15]. …”
mentioning
confidence: 99%